Diseño Y Construcción De Prototipo De Una Cortadora De Adoquines (2023)
The purpose of this research is to design and build a specialized cutting machine for Spanish-type terracotta pavers with approximate dimensions of 20 cm x 10 cm x 8 cm and a resistance equivalent to 61 MPa. The ability to cut this material also allows for cutting smaller materials with lower resistance.